Is ultrasound‐guided fine needle aspiration biopsy of axillary lymph nodes a viable alternative to sentinel lymph node biopsy?. Issue 10 (15th July 2021) - Astvatsaturyan, Kristine; Ramazyan, Arsen; Bose, Shikha
Abstract: Background: Axillary lymph node (ALN) ultrasound‐guided fine needle aspiration biopsy ( US‐FNAB), a minimally invasive procedure, may be used for the preoperative evaluation of ALN status of breast cancer patients. Despite the relative ease of use and low cost, paucity of comparative studies and variation in the reported sensitivity of FNAB preclude its clinical utility in evaluation of ALNs. This study aims to determine the accuracy of US‐FNAB in detecting metastasis in ALN pre‐operatively and to assess US‐FNAB as a viable alternative to sentinel lymph node (SLN) excision. Methods: The 228 consecutive ALN US‐FNABs with subsequent histologic follow up performed from 2005 to 2020 in patients with breast carcinoma were retrospectively evaluated. FNAB results were correlated with histologic diagnosis. Sensitivity, specificity, accuracy, and risk of malignancy of FNAB were calculated. Results: 157/228 (69%) FNABs were concordant with histology, 37/228 (16%) discordant. Positive FNAB findings correlated with primary tumor size, grade, number of metastatic lymph nodes and size of metastases. FNAB with negative diagnosis carried a 22% risk of malignancy, atypical 43%, suspicious 80%, and positive a 100% risk of malignancy (100% positive predictive value [PPV]). The sensitivity and specificity were 78% and 95% respectively; accuracy was 77%. SLN biopsy was avoided in all 82 (36%) cases with positive FNAB results. Conclusion: Negative FNAB result does not exclude metastatic carcinoma. With 100% PPV, full ALN dissection and/or neoadjuvant chemotherapy can be safely planned after a positive FNAB result, avoiding SLN biopsy, reducing management costs and shortening time interval to definitive therapy.